2021
DOI: 10.1038/s41598-021-91543-2
|View full text |Cite
|
Sign up to set email alerts
|

Fracture heat map of the facial skull demonstrates a danger zone of concomitant cervical spine injuries

Abstract: Concomitant maxillofacial and cervical spine injuries occur in 0.8–12% of the cases. We examined the relation of injury localization and the probability of cervical spine fracture. A retrospective study was conducted on patients that have been treated at Dortmund General Hospital for injuries both to the maxillofacial region and to the cervical spine between January 1st, 2007 and December 31th, 2017. Descriptive statistical methods were used to describe the correlation of cervical spine injuries with gender, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Ruslin et al 37 found zygomatic fractures to be the most common sport‐related fracture, further emphasizing the need for further work‐up and perhaps long‐term follow‐up for the development of TBI and related complications among athletes with zygomatic fractures. The multivariable analysis strengthens previous findings, demonstrating that zygomatic fractures may be linked to brain injury 38 and cervical spine injury 39 . Zygomatic fractures presumably require high energy, as other facial fractures frequently accompany them 39 .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Ruslin et al 37 found zygomatic fractures to be the most common sport‐related fracture, further emphasizing the need for further work‐up and perhaps long‐term follow‐up for the development of TBI and related complications among athletes with zygomatic fractures. The multivariable analysis strengthens previous findings, demonstrating that zygomatic fractures may be linked to brain injury 38 and cervical spine injury 39 . Zygomatic fractures presumably require high energy, as other facial fractures frequently accompany them 39 .…”
Section: Discussionsupporting
confidence: 82%
“…The multivariable analysis strengthens previous findings, demonstrating that zygomatic fractures may be linked to brain injury 38 and cervical spine injury. 39 Zygomatic fractures presumably require high energy, as other facial fractures frequently accompany them. 39 Błaszczyk et al 40 further demonstrated that craniocerebral injury is commonly observed in trauma mechanisms, including upper facial dislocation or extensive impact in the lateral face with involvement of the zygoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation